2015
DOI: 10.1364/josaa.32.001888
|View full text |Cite
|
Sign up to set email alerts
|

Detection and estimation of liquid flow through a pipe in a tissue-like object with ultrasound-assisted diffuse correlation spectroscopy

Abstract: Using coherent light interrogating a turbid object perturbed by a focused ultrasound (US) beam, we demonstrate localized measurement of dynamics in the focal region, termed the region-of-interest (ROI), from the decay of the modulation in intensity autocorrelation of light. When the ROI contains a pipe flow, the decay is shown to be sensitive to the average flow velocity from which the mean-squared displacement (MSD) of the scattering centers in the flow can be estimated. While the MSD estimated is seen to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…DCS is a noninvasive optical method that quantitatively measures tissue BF using speckle correlation techniques. 39,40,[42][43][44][45][46] Herein, aspects of this technique relevant to our study are highlighted; for additional details, the reader should consult comprehensive reviews and papers. 7,[36][37][38][39][40] DCS measures the temporal intensity fluctuations of coherent near-infrared (NIR) light that has multiply scattered from moving red blood cells in tissue.…”
Section: Diffuse Correlation Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…DCS is a noninvasive optical method that quantitatively measures tissue BF using speckle correlation techniques. 39,40,[42][43][44][45][46] Herein, aspects of this technique relevant to our study are highlighted; for additional details, the reader should consult comprehensive reviews and papers. 7,[36][37][38][39][40] DCS measures the temporal intensity fluctuations of coherent near-infrared (NIR) light that has multiply scattered from moving red blood cells in tissue.…”
Section: Diffuse Correlation Spectroscopymentioning
confidence: 99%
“…41 DCS is a simple noninvasive technique that derives flow information from measurements of the temporal intensity fluctuations of multiply scattered light. 39,40,[42][43][44][45][46] The DCS BFI has been validated against a plethora of gold-standard techniques; 7,[47][48][49][50][51][52] in these studies, the BFI and especially its variation were demonstrated to be approximately proportional to true BF in a range of subjects and tissue types. However, clinical interpretation of the DCS BFI is complicated by its unusual units of [cm 2 ∕s].…”
Section: Introductionmentioning
confidence: 99%
“…∆r 2 (τ) is a correlation-time (τ) dependent term and represents the ensemble-averaged, mean-squared displacement of moving scatterers in time τ. k 0 is the wave-vector associated with the laser source and S(r) describes the spatial geometry of the source to be modeled [15]. Two models are commonly used for ∆r 2 (τ) : the Brownian flow model (where ∆r 2 (τ) = 6D B τ) with Brownian flow coefficient D B ; the random flow model (where ∆r 2 (τ) = V 2 τ 2 ) where V is the average volumetric flow-speed of the scattering particles [5,15,16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of ultrasonically modulated light has been suggested for sensing the flow of scattering particles. Chandran et al [24] demonstrated that the temporal fluctuations in the reflected light intensity can be linked to the flow speed of the moving particles in the US focus. Tsalach et al [25] proposed the use of ultrasonic modulation of light for depth selective flow measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we demonstrate a sim-ple flow imaging method that relies on comparing UOT images taken with a short and a long integration time of the CCD. In comparison with work of Chandran et al and Tsalach et al [24,25] on sensing flow of scattering particle using UOT using a single, fast photodetectors, we employ a parallel detection scheme with a CCD camera. Our method relates to these studies as LASCA relates to laser Doppler flowmetry [26].…”
Section: Introductionmentioning
confidence: 99%